2006
DOI: 10.1590/s1413-81232006000400020
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdades sociais no uso de internações hospitalares no Brasil: o que mudou entre 1998 e 2003

Abstract: O objetivo deste artigo foi comparar os fatores associados às internações hospitalares no Brasil em 1998 e 2003. A Pesquisa Nacional por Amostra de Domicílios de 2003 foi analisada utilizando modelo de regressão logística com pesos normalizados, tendo o Modelo Comportamental de Andersen como base teórica, e os resultados foram comparados aos da PNAD 1998 anteriormente publicados. Houve diminuição dos coeficientes de internação para mulheres em idade reprodutiva e para idosos; e aumento dos coeficientes para cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 2 publications
0
4
1
9
Order By: Relevance
“…Our data show greater occurrence of hospitalization among subjects with fi ve to seven years of study, a difference that was not observed by either Castro 9 or Garbinato. 11 In adjusted analysis, smoking was associated with hospitalization only among men, former smokers showing higher frequency of hospitalization.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our data show greater occurrence of hospitalization among subjects with fi ve to seven years of study, a difference that was not observed by either Castro 9 or Garbinato. 11 In adjusted analysis, smoking was associated with hospitalization only among men, former smokers showing higher frequency of hospitalization.…”
Section: Discussioncontrasting
confidence: 59%
“…In Brazil, lower-income populations show greater self-reported morbidity, 22 To be continued which would justify a greater frequency of hospitalization among these individuals. On the other hand, Castro 9 has shown that socioeconomic differences in hospital utilization are not as noticeable as they are for other types of health care. The reason for these differences could be related to antagonistic mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…Data from the 2003 Brazilian National Household Survey showed 72.9% of all clinical hospitalizations were in the SUS and were used to estimate hospitalization rates in the private sector. 4 Meningitis is a mandatory notifi able disease in Brazil, and data from the Notifi able Diseases Database (Sistema de Informação de Agravos de Notifi cação -SINAN) for the same period were also analyzed. SINAN database includes aggregate data on population frequency of notifi able diseases and their outcomes according to age group, clinical syndromes and etiological agents, and good quality information on meningitis.…”
Section: Methodsmentioning
confidence: 99%
“…Entretanto, outros estudos apontam que a diminuição no número de hospitais da rede SUS foi acompanhada por aumento da participação do SUS no volume das internações (Castro, 2006e Porto et al, 2006 com tendência para diminuição nos tempos de permanência (Castro, 2006), observando-se padrão semelhante na busca de serviços dos usuários SUS e dos não SUS (Ribeiro et al, 2006). Essas questões remetem a aspectos relacionados à implantação do sistema de saúde, em especial à evolução do modelo assistencial.…”
Section: Assistência Hospitalar No Brasilunclassified